Analysis of Public Policy Implementation in Poverty Alleviation in Urban Areas - Sinaga, Indri Lasti; Rotua, Bintra (IHSA Institute, 2024)
This research examines the implementation of public policies aimed at alleviating urban poverty, focusing on the effectiveness of strategies in diverse urban contexts. Utilizing a mixed-methods approach, including quantitative analysis and qualitative case studies, the study investigates key factors influencing policy outcomes. Findings underscore the critical role of community engagement, highlighting that policies involving active participation of urban residents tend to be more effective and sustainable. Additionally, the study identifies strong local governance as essential, emphasizing transparent and accountable management of resources to enhance policy impact. Unexpectedly, the study reveals the significant contribution of informal networks in supplementing formal policy efforts, suggesting a need to integrate these social dynamics into policy frameworks.